Analisis Employee Engagement Terhadap Motivasi Dan Implikasinya Pada Turnover Intention Di Rumah Sakit Hermina Kabupaten Karawang - Putri, Ria Hutami; Mulyani, Sri Rochani; Kadarisman, Sumeidi; Djogo, Y Ony; Panjaitan, Biller (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2024)
This study examines the influence of employee engagement and motivation on turnover intention at Hermina Hospital Karawang Regency. Using a quantitative approach with descriptive and verifiable analysis, this study involved 132 employees. The descriptive results showed that the respondents' assessment was in the good category, although there were some low scores that needed to be considered. Verifiable analysis showed a positive influence between variables, with a direct influence of 11.97% and an indirect influence of 3.76%. Work motivation as an intervening variable is not able to mediate the relationship between employee engagement and turnover intention. The results of the t-test showed that employee engagement had a significant positive effect on work motivation and turnover intention, while motivation had a positive but not significant effect on turnover intention. This research expected contribute to hospital management policies to reduce turnover intention.